A Política de indexação para a organização do conhecimento no contexto organizacional: estudo de caso no SIBI-UFPA - FONSECA, Luciana Di Paula Andrade (Universidade Federal do Pará, 2024)
This research is part of the research field of Information Science, in the Knowledge Organization subarea and aims to discuss the importance of indexing policy in university libraries. The research is justified by the need to investigate aspects of organizational infrastructure for indexing policy development for the organization of knowledge in the physical and social space of university libraries. The research problem is: how can an indexing policy contribute to the organization of knowledge in the sectorial libraries of the Federal University of Pará? The general objective: to contribute to discussions on the relevance of the indexing policy for the organization of knowledge in sectorial libraries of the Federal University of Pará. The specific objectives are: a) to carry out a bibliographic survey on the topics of knowledge organization and representation, indexing, indexing policy, information retrieval and the like; b) Conduct a diagnostic study of the organizational infrastructure of Federal University of Pará libraries; c) Investigate the elements of indexing policy from the catalogers in the Library System of the Federal University of Pará. Methodologically, the research is characterized as a case study of an exploratory nature with qualitative analysis of the data, in which the instruments of data collection are: bibliographic research in databases and a questionnaire, sent through Google forms to the professional catalogers of the Library System of the Federal University of Pará. Results: the inexistence of an indexing policy was identified out of a sample of twelve libraries that participated in the research, motivating the non-standardization in the use strategies of Subject Analysis and Cataloging Translation. However, based on the daily experiences of the catalogers, the following elements were found: human resources, clientele, subject coverage, selection and acquisition of source documents, level of exhaustiveness, indexing process, documentation language, system evaluation and search strategies, which are part of an indexing policy. It was concluded that despite the non-formalization of the indexing policy, the integrated network of libraries has subsidies and elements for the formalization of guidelines, since the indexing policy in the integrated network can be an ally in the standardization of the indexing process among cataloging professionals, as well as in carrying out training programs aiming subject cataloging, with guidelines on the use of retrospective conversion of bibliographic records, use of catalogs and databases in subject cataloging, giving the possibility of using this research as a model for the elaboration of an indexing policy, in addition to contributing to new studies on the topic of indexing policy in the Brazilian context.